Effectiveness of the Use of Media and Learning Models in Improving Students' Mathematical Communication Skills: Systematic Literature Review - Prasojo, Teguh; Hidayah, Isti (Journal of Education Method and Learning Strategy, 2024)
SLR is researched to describe and find out the level of students' numerical communication capacity. Several parties have utilized a variety of learning materials and learning models to achieve the desired goals. The purpose of this study is to find out which learning tools and models can increase the scientific capacity of students. This question is divided into two tables, namely the media table and the strategy table. Analysts use proper writing audit frameworks to investigate existing diries. From the important articles, it can be concluded that a typical learning model can be utilized in learning materials aimed at supporting the advancement of scientific communication skills.